Experimental investigation into the influence of zeolite addition on shallow foundations behavior placed on coastal sand of Mazandaran Sea - Sina Salamatpoor (Iranian Society of Structrual Engineering (ISSE), 2021)
The shortcoming of loose sandy soils in terms of shear strength besides placement of a huge number of structures on them drive the critical requirement for exploring the shallow foundations treatment, their positioning and shapes. In this regard, stabilization of loose sandy soils through fabricating cement and an appropriate additive is one of a promising solution. Hence, in this study, a series of unconfined compressive strength tests have been conducted to find out the mechanical properties of zeolite cemented sand composites. Afterwards, 1g small scale tests have been performed to measure the behavior of shallow foundations placed on the stabilized ground. The main aims of this study are enhancing the bearing capacity and conversely decreasing the settlement of foundations attributed to the chemical reactions between sand, cement and zeolite particles. The results demonstrate that placing a zeolite pad with B/3 thickness underneath the shallow foundation, which contain 3% and 7% cement content, increases their bearing capacity in a range between 11% and 23% respectively compared to those of without a zeolite pad. This is followed by respectively 44% and 67% enhancement in the bearing capacity through doubling the thickness of the zeolite pad. Considering the cement content as a comparing factor between the samples, increasing in the resistant coefficient is in a range between 9% to 23%, while it is constantly 6% for the decreasing coefficient. In summary, this stabilization approach improves the behavior of shallow footing on loose soils.